Pola Perkembangan Anak Berkebutuhan Khusus Yang Bersekolah Di Sekolah Inklusi - Luqmanul Hakim; Murfiah Dewi Wulandasri; Darsinah Darsinah (Jurnal Ilmiah Wahana Pendidikan, 2022)
Children with special needs have the right to a proper education. The aims of this study were: 1) Knowing the characteristics and abilities of children with special needs in MI Tholabiyah Salary, 2) Knowing the development of children with special needs at MI Tholabiyah Salary, 3) Knowing the positive and negative impacts of children with special needs in MI Tholabiyah Salary. This research uses qualitative research with descriptive qualitative approach. Data was collected by observation and interviews. The results of this study are children with special needs have abilities below the average compared to others, but they still experience significant development. The presence of children with special needs has a positive and negative impact on their peers in the educational environment.